Spatial planning for non-Muslim access in a Masjid - Amran, Maryam Ilhami; Abdul Rahim, Asiah (Abdullatif Al Fozan Award for Mosque Architecture and Institut Terjemahan & Buku Malaysia Berhad, 2019)
INTRODUCTION MASJID is a place where purity and sanctity are kept for the Muslim to perform their ibadah. Nevertheless, the role of masjid also expanded to respond to the teachings of Prophet Muhammad (PBUH) that masjid also act as a centre that could provide services for the non-Muslims. In the Qur’an verse (2:143) – “And thus we have made you a just community that you will be witnesses over the people and the Messenger will be a witness over you” – every aspect of life people live in a community, where each and every one depend on one another. The Prophet’s Masjid was a place for shelter to those who were in dire need where lodging were provided, a place for Prophet’s (PBUH) guest who were non-Muslim were welcomed and a place for discussion or dialogue for the non-Muslim (Omer, 2013). Under the Irsyad Al-Fatwa number 271: “The Ruling for Non-Muslim Entering the Mosque”, non-Muslim are permissible to enter masjid (Tarmizi, 2018). However, the ruling is applicable on several conditions, which are to follow the dos and don’ts while visiting the masjid (Omer, 2018).